2008
DOI: 10.1161/circresaha.107.163428
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Cardiomyocyte Proliferation and Myocardial Growth During Development by FOXO Transcription Factors

Abstract: Abstract-Cardiomyocytes actively proliferate during embryogenesis and withdraw from the cell cycle during neonatal stages. FOXO (Forkhead O) transcription factors are a direct target of phosphatidylinositol-3 kinase/AKT signaling in skeletal and smooth muscle and regulate expression of the Cip/Kip family of cyclin kinase inhibitors in other cell types; however, the interaction of phosphatidylinositol-3 kinase/AKT signaling, FOXO transcription factors, and cyclin kinase inhibitor expression has not been reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
163
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 191 publications
(176 citation statements)
references
References 34 publications
6
163
0
3
Order By: Relevance
“…In some experiments, the inhibitor of autophagosome formation, 3-methyladenine (3MA, 10 M), was added to determine the requirement for autophagy in starvation-induced cardiomyocyte cell size reduction. Adenoviral infections were performed as described previously (27) with wild-type (WT), constitutively active (CA) FoxO1 or dominant negative FoxO1 (⌬256) obtained from D. Accili (35) and wild-type (WT) or CA-FoxO3 obtained from K. Walsh (26). Infection with cytomegalovirus ␤-galactosidase virus was used as a control for all experiments.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In some experiments, the inhibitor of autophagosome formation, 3-methyladenine (3MA, 10 M), was added to determine the requirement for autophagy in starvation-induced cardiomyocyte cell size reduction. Adenoviral infections were performed as described previously (27) with wild-type (WT), constitutively active (CA) FoxO1 or dominant negative FoxO1 (⌬256) obtained from D. Accili (35) and wild-type (WT) or CA-FoxO3 obtained from K. Walsh (26). Infection with cytomegalovirus ␤-galactosidase virus was used as a control for all experiments.…”
Section: Methodsmentioning
confidence: 99%
“…The FoxO subfamily of transcription factors consists of FoxO1, FoxO3, and FoxO4, which are subject to inhibition by growth factors, including insulin and insulin-like growth factor-1 (25). During growth factor limitation, the inhibition of FoxO activity by phosphatidylinositol 3-kinase/AKT is relieved, and the dephosphorylated FoxO transcription factors are activated and become localized to the nucleus (23,26,27). Sirt1, a mammalian ortholog of NAD ϩ -dependent protein deacetylase, Sir2, promotes the activity of FoxO transcription factors by deacety-lation under conditions of oxidative stress (24).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The Forkhead box O (FOXO) family of transcription factors plays an important role in cellular metabolism, differentiation, and muscle atrophy in mammals [14,15] . The FOXO1 transcription factor has been suggested to directly modulate the expression of the MuRF1 protein during muscle atrophy [16,17] .…”
Section: Wwwchinapharcom Chen Bl Et Almentioning
confidence: 99%
“…The FOXO1 transcription factor has been suggested to directly modulate the expression of the MuRF1 protein during muscle atrophy [16,17] . Recent studies have indicated that FOXO1 can suppress cardiomyocyte proliferation and blunt cardiac hypertrophy [15,18] . Thus, atrophy-related FOXO1/MuRF1 pathways may serve as a target for reversing remodeling of the hypertrophied heart.…”
Section: Wwwchinapharcom Chen Bl Et Almentioning
confidence: 99%